1998
DOI: 10.1080/15216549800204102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aminoguanidine on lipid peroxidation and activities of antioxidant enzymes in the diabetic kidney

Abstract: SUMMARYThe aim of this study was to examine lipid peroxidation and activities of key antioxidant enzymes in kidneys of rats with streptozotocin (STZ)-induced diabetes and the effect of aminoguanidine on diabetes-induced alterations. Three groups, 6 rats each, were studied: control animals, not treated diabetic rats and rats treated with aminoguanidine (AG; 1 g/liter of drinking water) After 6 and 12 weeks the animals were sacrificed and lipid peroxidation products and activities of antioxidant enzymes were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…1). The last 3 compounds were used as reference compounds: both aminoguanidine 28,29) and pyridoxamine, 30,31) known to be beneficial in preventing diabetic complications in animals, have been reported to have antioxidant activity. The 4 chitooligosaccharides studied were all inhibitory against benzoate hydroxylation induced by H 2 O 2 , with chitobiose having a markedly high potency; whereas the other sugars studied did not show the inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…1). The last 3 compounds were used as reference compounds: both aminoguanidine 28,29) and pyridoxamine, 30,31) known to be beneficial in preventing diabetic complications in animals, have been reported to have antioxidant activity. The 4 chitooligosaccharides studied were all inhibitory against benzoate hydroxylation induced by H 2 O 2 , with chitobiose having a markedly high potency; whereas the other sugars studied did not show the inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…2 Diabetes also disturbs natural antioxidant defence systems, changing antioxidant enzyme activities in various tissues including aorta, 3,4 heart, 3,5,6 liver, [5][6][7] lung 8 and kidney. 9 Previous studies have shown that antioxidants, including vitamins C, E, A, 10,11 coenzyme Q10, 6 probucol, 12 and alpha-lipoic acid, 4 have some capacity in preventing or reversing disturbances in tissue antioxidant defence in diabetic animals. On the other hand, an increase in circulating lipids may be a reason for their increased peroxidation in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Free MDA concentrations higher than 50 nM would cause a concurrent decrease in the half-life of the collagen cross-link. Where it is measured, MDA concentration tends to double for diabetic subjects (27,31,32).…”
Section: Figmentioning
confidence: 99%